Ризик регулювання у процесі планування виробничо-господарської діяльності підприємства - Лакіза, В. В. (Видавництво Львівської політехніки, 2015)
Розглянуто регулювання стосовно функції планування, висвітлено причини появи ризику корегувальних заходів у процесі планування; виявлено та ідентифіковано фактори ризику та підходи для оцінювання ризику регулювання; запропоновано поділ ризиків регулювання за характером дії, визначення міри ризику та управління ризиком регулювання; сформовано послідовність розроблення корегувальних заходів у процесі стратегічного планування з урахуванням можливості виникнення ризиків регулювання; виділено суб’єктивні перепони для здійснення ефективного стратегічного планування. Regulating is considered in the context of planning functions; the definition of a separate group of risks of regulating in the context of the planning function in general and strategic planning in particular is offered. There are also considered risks that inevitably arise in the process of developing and implementing production and sales plans of enterprises. The causes of risks are explained (unpredictable changes in both external and internal environment of the enterprise). Risk factors and approaches for assessing the risk of regulating are detected and identified; the sequence of developing corrective measures in the process of strategic planning with the account of regulating risks is formed. The following approaches to risk assessment are reviewed: elaboration of all possible alternative regulatory conditions of completing regulating measures; identification of the most vulnerable points in regulatory actions; analysis of regulatory measures sensitivity to perturbating effects. Regulation risk management is defined as the process of preparation and implementation of measures aimed at reducing threats of taking wrong decisions and possible negative consequences of unwanted developments in the process of implementing the decisions taken. It should be based on the concept of acceptable risk, which reduces the possibility of its growth and brings the risk to an acceptable value. There are four methods of risk management: avoidance, localization, dissipation (distribution, diversification) and compensation. It is indicated that risk management is conducted on two levels - a controlled and controlling ones. Risk analysis involves the following steps: forming the final list of potentially unwanted events; defining a set of risk factors and their combinations based on certain qualitative and quantitative values and its particular indicators; evaluating and interpreting the obtained risk indicators values of an initially chosen corrective measure. The following subjective obstacles for effective strategic planning can be defined: excessive pressure, privilege of short-term indicators over long-term ones, manager’s personality traits, planning specialist’s personality traits. It is noted that an enterprise cannot fully eliminate the risk of its activities, including the risk of ineffective regulating actions, but is able to manage risks through their effective prediction.
Risk of regulating in the process of planning productive and economic activities of enterprise
Keywords: ризик; регулювання; ризик регулювання; планування; risk; adjusting; risk of adjusting; planning